Emerging Cell-Based Therapies in Chronic Lung Diseases: What About Asthma? - Andressa Daronco Cereta; Vinícius Rosa Oliveira; Vinícius Rosa Oliveira; Ivan Peres Costa; João Pedro Ribeiro Afonso; Adriano Luís Fonseca; Alan Robson Trigueiro de Souza; Guilherme Augusto Moreira Silva; Diego A. C. P. G. Mello; Luis Vicente Franco de Oliveira; Renata Kelly da Palma; Renata Kelly da Palma; et al. (Frontiers Media S.A., 2021)
Asthma is a widespread disease characterized by chronic airway inflammation. It causes substantial disability, impaired quality of life, and avoidable deaths around the world. The main treatment for asthmatic patients is the administration of corticosteroids, which improves the quality of life; however, prolonged use of corticosteroids interferes with extracellular matrix elements. Therefore, cell-based therapies are emerging as a novel therapeutic contribution to tissue regeneration for lung diseases. This study aimed to summarize the advancements in cell therapy involving mesenchymal stromal cells, extracellular vesicles, and immune cells such as T-cells in asthma. Our findings provide evidence that the use of mesenchymal stem cells, their derivatives, and immune cells such as T-cells are an initial milestone to understand how emergent cell-based therapies are effective to face the challenges in the development, progression, and management of asthma, thus improving the quality of life.